A statistical quality control study on Del Monte Philippines, Inc. - Tan, Katherine (College of Engineering, 2005)
At the onset of the semester, the group began to scout for companies that will allow for an Industrial Quality Control Study. The group was faced with a few alternatives, but it all boiled down to Del Monte Philippines Incorporated (DMPI). Then, the group started its initial plant visits at DMPI's plant location in Las Pinas. DMPI produces many kind of consumer products, and the 115 and 200 grams Stand-up-pouches Tomato Sauce were chosen as the product in focus. After knowing that the production of this SUP Tomato Sauce are done by about 13 Toll Packers, the group also visited one of its Toll Packers, Innovative Packing Industries Corporation (IPIC) in Valenzuela. Then, the group concentrated this study within the SUPs produced in IPIC, because they produce bulk of the SUP Tomato Sauce for DMPI. DMPI allowed the use of the Net Weight Conformance of 115 grams and 200 grams SUP Tomato Sauce observed and recorded during 2003 by the IPIC inspectors using SPC methods. The group also went around its plant facilities to know how their production operates. The group, during the whole study at Del Monte Philippines' Toll Packing Operations, focused on applying statistical tools to improving the company's quality especially on the net weight conformance of its tomato sauce stand-up-pouches (SUPs). The group started by documenting DMPI's operations, toll packing facilities, history, mission and vision and other information useful in analyzing the company's quality. The documentation focused on the equipment used, the company's production process, inspection process and methods of ensuring quality. Through this, the group wanted to record the company;s current practices and focus with respect to quality control. Problem analysis was then done to identify problem areas through observation, analysis of the system documented, and by recommendation of the company itself. As the main problem identification tools, the group was aided by Ishikawa diagrams, FMEA, Stream Diagnostic Chart. Consequently, the problems identified were the used as the focal point of analyses and recommendations. This was followed by cost analysis of the process to see how much is lost due to quality problems. The group discovered that this cost was significant due to the high volume involved an that the costs rely much on process variability.